Stress and eating behavior (Research, Society and Development, 2021)
Introduction: we can define as a brief concept of stress the understanding as sequences of reactions, which transform the physical and psychological integrity, which terrify the balance of the organism (homeostasis). Stress is an important factor in the development of addiction and relapse of addiction and can contribute to an increased risk of obesity and other metabolic diseases. Uncontrollable stress changes eating patterns and the overhang and consumption of hyper-palatable foods; over time, this could lead to changes in the allostatic load and trigger neurobiological adaptations that promote an increasingly compulsive behavior. Methodology: bibliographic research was chosen, developed from material already prepared, consisting mainly of books and scientific articles. Results: In this work, it was demonstrated that stress has been considered a critical risk factor in the development of addictive disorders and relapse to addictive behaviors. However, few studies have reviewed the links between stress and food intake, particularly hyper-palatable or “comfortable” foods that can be consumed to reduce stress. Conclusion: We can analyze that the perception and assessment of stress really depends on specific aspects of the presentation of external or internal stimuli and can be moderated or mediated by personality traits, emotional state and physiological responses that, together, contribute to the experience of suffering.